Scale Up Nanostructured Lipid Carrier (NLC) Koenzim Q10 Menggunakan Matriks Lipid Asam Stearat-Isopropil Palmitat - Gracia Juanita; Ni Luh Dewi Aryani (Universitas Pahlawan Tuanku Tambusai, 2023)
Overexposure to the sun can lead to the production of reactive oxygen species (ROS), which accelerates the aging process of the skin. The formation of ROS can be prevented with antioxidant compounds. Coenzyme Q10 is a lipophilic antioxidant because it has 10 isoprene side chains, causing coenzyme Q10 to have low skin penetration ability. Thus, the Coenzyme Q10 Nanostructured Lipid Carrier (NLC) technology was created to improve coenzyme Q10's skin penetration. This research examined the physicochemical properties of scaled-up Coenzyme Q10 NLC formulation. The method used is High Shear Homogenization HSH), by testing two formulas, namely F1 with 20% surfactant content and 30% surfactant F2. The results obtained for the physicochemical characteristics of F1 and F2 were seen from the organoleptic parameters which were yellowish in color, semisolid, and had a characteristic odor of fat; viscosity (825.60±537.63cps; 2588.33±584.42cps), pseudoplastic flow properties; pH (5,74±0,057; 5,80±0,021), particle size (592,33±158,19nm; 257,5±39,53nm), zeta potential (-12,73±18.5mV; -36, 1±20.91mV), polydispersity index (0,461±0,129; 0,223±0,104), spherical and smooth surface morphology; decreased and increased peak height at º2Th (21.5645, 23.005; 18.9246, 22.9967), and no interaction was found between the active ingredient and the carrier. This study finds that a successful formulation of coenzyme Q10 NLC has been made.